Perencanaan Pembangunan Dalam Perspektif Administrasi Publik: Konsep, Proses, Dan Tantangan Di Era Desentralisasi - Abubakar, Zulkarnain; Monulit, Siti Aisyah; Pilobu, Yulandari; Adabu, Putri (JPS: Journal of Publicness Studies, 2026)
This article examines development planning from the perspective of public administration, focusing on concepts, processes, institutional mechanisms, and challenges in the era of decentralization in Indonesia. The study uses a qualitative approach through literature review by analyzing books, scientific journals, regulations, and policy documents related to development planning and public administration. The findings indicate that development planning is not merely a technical activity but also a political and administrative process involving multiple stakeholders. The implementation of the National Development Planning System has provided a comprehensive framework for integrating national and regional planning; however, several challenges remain, including weak coordination among institutions, inconsistencies between planning and budgeting, limited institutional capacity in local governments, and the dominance of political interests in decision-making processes. The study also highlights the importance of good governance principles, such as transparency, accountability, participation, and effectiveness, in improving the quality of development planning. Furthermore, digital transformation and evidence-based planning are identified as strategic approaches to strengthening planning systems in the modern era. The study concludes that reforming the development planning system requires strengthening institutional capacity, improving public participation, integrating planning and budgeting systems, and optimizing the use of information technology to achieve inclusive and sustainable development.